2021
DOI: 10.1021/acsaem.1c00159
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Conversion of Unsolvated Mg(B3H8)2 to BH4 in the Presence of MgH2

Abstract: In the search for energy storage materials, metal octahydrotriborates, M­(B3H8) n , n = 1 and 2, are promising candidates for applications such as stationary hydrogen storage and all-solid-state batteries. Therefore, we studied the thermal conversion of unsolvated Mg­(B3H8)2 to BH4 – as-synthesized and in the presence of MgH2. The conversion of our unsolvated Mg­(B3H8)2 starts at ∼100 °C and yields ∼22 wt % of BH4 – along with the formation of (closo-hydro)­borates and volatile boranes. This loss of boron (B) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 78 publications
0
3
0
Order By: Relevance
“…Thermogravimetry (TG) experiments [59] revealed a 30 wt % mass loss setting in above ca 80 • C corresponding to the evolution of B 2 H 6 , B 5 H 9 and H 2 . The residual solid after heating to 200 • C was a mixture of mainly Mg(BH 4 ) 2 , Mg(B 10 H 10 ), and Mg(B 12 H 12 ), and the combined evolution of H 2 , B 2 H 6 , and B 5 H 9 was confirmed by mass spectrometry [60]. The addition of activated (ball-milled) MgH 2 to Mg(B 3 H 8 ) 2 results in a strong reduction in borane evolution and up to 88% conversion back to Mg(BH 4 ) 2 at 100 • C. The presence of activated MgH 2 thus substantially decreases the formation of (closo-hydro)borates and provides the necessary hydrogen for the conversion of B 3 H 8 − back into BH 4 − .…”
Section: Magnesium Borohydridementioning
confidence: 88%
“…Thermogravimetry (TG) experiments [59] revealed a 30 wt % mass loss setting in above ca 80 • C corresponding to the evolution of B 2 H 6 , B 5 H 9 and H 2 . The residual solid after heating to 200 • C was a mixture of mainly Mg(BH 4 ) 2 , Mg(B 10 H 10 ), and Mg(B 12 H 12 ), and the combined evolution of H 2 , B 2 H 6 , and B 5 H 9 was confirmed by mass spectrometry [60]. The addition of activated (ball-milled) MgH 2 to Mg(B 3 H 8 ) 2 results in a strong reduction in borane evolution and up to 88% conversion back to Mg(BH 4 ) 2 at 100 • C. The presence of activated MgH 2 thus substantially decreases the formation of (closo-hydro)borates and provides the necessary hydrogen for the conversion of B 3 H 8 − back into BH 4 − .…”
Section: Magnesium Borohydridementioning
confidence: 88%
“…The dynamics and lack of three-dimensional crystallinity are likely reasons why B 3 H − 8 forms during dehydrogenation of Mg(BH 4 ) 2 , despite unfavourable thermodynamic predictions [222]. Similarly, another recent DFT study confirmed that the solid-state reactive environment provides a unique energy landscape that can stabilize formation of B 6) [224]. This is surprising given that the reverse reaction, formation of Mg(B 3 H 8 ) 2 , is observed during the decomposition of Mg(BH 4 ) 2 .…”
Section: Boratesmentioning
confidence: 99%
“…B 3 H − 8 has not been observed during KBH 4 dehydrogenation because the decomposition occurs at temperatures above which KB 3 H 8 is stable.The thermal decomposition of KB 3 H 8 and Mg(B 3 H 8 ) 2 shows some similarities, but their reaction with hydrogen and metal hydrides is noticeably different, as shown in figure6. Mg(B 3 H 8 ) 2 begins to lose H 2 at ≈100 • C[224], while for KB 3 H 8 it initiates at ≈150 • C-200 • C[220]. Both disproportionate into the corresponding borohydride and some combination of closo-borates B 10 H 10 2− and B 12 H 12 2− .…”
mentioning
confidence: 99%
“…Notably, the weak features at 2130 and 2075 cm −1 not present in the pristine Mg(BH 4 ) 2 or H 3 BO 3 / Mg(BO 2 ) 2 are suggesting that the boranes with bridged hydrogen atoms in the structure are formed at this stage. These could be (B 2 H 7 ) − , (B 3 H 7 ) 2− [22], (B 3 H 8 ) − [22,35,36], (B 4 H 10 ) 2− [18], etc. These peaks are accompanied by the peaks at > 2300 cm −1 , which are characteristic for the stretching of terminal hydrogen atoms of such boron hydride anions and Mg-H-B stretching [37].…”
Section: Groupmentioning
confidence: 99%